A-ZHLS: adaptive ZHLS routing protocol for heterogeneous mobile adhoc networks - V. Narayana, M; Atmakuri, Aparnarajesh (International Journal of Engineering and Technology, 2018)
The routing protocols in MANET are mainly classified into two typeâ€™s i.e. pro-active and reactive based protocol based on its problems in the network. One of the prime and foremost issues, which have gained a lot of scope, is its dynamic nature of the networks i.e. the stability of nodes is not guaranteed in the network. Hence, this leads to loss of data packets that needs for its retransmission. Many advancements and Novel protocols have been devised in recent years for efficiency and effectiveness in the ad hoc networks. However, hybrid routing proto-cols that inculcates the nature of reactive and proactive has gained a lot of importance. ZHLS is one of the Hybrid routing protocol, and is a two tier hierarchal routing that divides the area into zones in which mobile nodes move randomly. The process of promoting ZHLS protocol is purely based on homogeneous scenarios which mean the nodes in the network are statistically identical, but there is lack of studies for heterogeneous set-up where mobile nodes act in a different way in an identical network. In this paper, we try to propose a novel approach known as â€œAdaptive-ZHLS: AZHLSâ€ that can be suitable for heterogeneous scenarios. Experimental set up and simulated results will show that AZHLS provides higher packet delivery fraction as compared with the traditional one.Â